Can Control Infections Slow Down the Progression of Alzheimer’s Disease? Talking About the Role of Infections in Alzheimer’s Disease - Shi, Mingchao; Li, Chunrong; Tian, Xiaoping; Chu, Fengna; Zhu, Jie (Frontiers in Aging Neuroscience, 2021)
Alzheimer´s disease (AD) as the most common age-related dementia affects more than 40 million people in the world representing a global public health priority. However, the pathogenesis of AD is complex and it remains unclear. Over past decades all efforts made in the treatments of AD with targeting the pathogenic amyloid β (Aβ), neurofibrillary tangles and misfolded tau protein were failed. Recently many studies hint that infections and chronic inflammation caused by infections are crucial risk factors for AD development and progress. In the review, we analyzed the role and mechanisms of infections caused by bacteria, viruses and other pathogens in the pathogenesis of AD and its animal models, and explored the therapeutic possibility with anti-infections for AD. However, basis on the published data, it is still difficult to determine their causal relationship between infection and AD due to contradictory results. We think that the role of infection in the pathogenesis of AD should not be ignored, even though infection does not necessarily cause AD, it may act as accelerators in AD at least. The longitudinal study and randomized controlled trials in humans are essential to determine the role of infection in AD and to clarify the links between infection and main pathological features of AD. Finding targeting infection drugs and identifying the time window applying antibacterial or antiviral intervention may be more promising for future clinical therapeutic strategies in AD.